Increased diagnosis of hepato-biliary-pancreatic cancer after cholecystectomy: a population-based study - Young Ae Kim; Hak Jun Kim; Mee Joo Kang; Sung-Sik Han; Hyeong Min Park; Sang-Jae Park (Scientific Reports)
Abstract Given the increasing trend of cholecystectomy, it is imperative to reassess surgical and surveillance strategies in consideration of the potential long-term risks for digestive tract cancers. The objective of this study was to assess the risk of gastrointestinal (GI) and hepato-biliary-pancreatic (HBP) cancer incidence after cholecystectomy. The data for this cohort study was obtained from the National Health Insurance Service database in Korea. 715,872 patients who underwent cholecystectomy between 2004 and 2020 were compared to 1,431,728 individuals who did not underwent cholecystectomy after age, sex, and year of cholecystectomy was matched. The overall incidence rate ratio (IRR) for all GI and HBP cancers was 1.08 (95% C.I., 1.06–1.10). Specifically, the risk of diagnosis of extrahepatic bile duct cancer (IRR 1.92), intrahepatic bile duct cancer (1.78), hepatocellular carcinoma (1.22), and pancreatic cancer (1.13) was significantly increased in the cholecystectomy group. The highest IRR was observed within the 1–3 years following cholecystectomy. Subsequently, the risk of diagnosis gradually decreased and returned to a level comparable to that of the matched control group after 5 to 10 years. In conclusion, hepato-biliary-pancreatic cancer are frequently diagnosed subsequent to cholecystectomy. Too short period of post-cholecystectomy follow-up may hinder monitoring of hepato-biliary-pancreatic cancer occurrence.